Breaking Beyond the Borders of the Brain: Self-Control as a Situated Ability - Yahya, Jumana (Frontiers in Psychology, 2021)
“I just couldn’t control myself” are the infamous last words of a person that did something that they knew they should not have done. Consistent self-control is difficult to achieve, but it is also instrumental in achieving ambitious goals. Traditionally, the key to self-control has been assumed to reside in the brain. Recently, an alternative has come to light through the emergence of situated theories of self-control, which emphasize the causal role of specific situated factors in producing successful self-control. Some clinical interventions for motivational or impulse control disorders also incorporate certain situated factors in therapeutic practices. Despite remaining a minority, situated views and practices based on these theories have planted the seeds of a paradigm shift in the self-control literature, moving away from the idea that self-control is an ability limited to the borders of the brain. The goal of this paper is to further motivate this paradigm shift by arguing that certain situated factors show strong promise as genuine causes of successful self-control, but this potential role is too often neglected by theorists and empirical researchers. I will present empirical evidence which suggests that three specific situated factors - clenched muscles, calming or anxiety-inducing environmental cues, and social trust - exhibit a specialized effect of increasing the likelihood of successful self-control. Adopting this situated view of the ability to regulate oneself works to reinforce and emphasize the emerging trend to design therapies based on situated cognition, makes self-control more accessible and less overwhelming for laypeople and those who struggle with impulse control disorders, and opens a new avenue of empirical investigation.